2022
DOI: 10.1007/s10597-021-00922-6
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Utility of Different Approaches to Violence Risk Assessment for Young Adults Receiving Treatment for Early Psychosis

Abstract: This pilot study examined violence risk assessment among a sample of young adults receiving treatment for early psychosis. In this study, thirty participants were assessed for violence risk at baseline. Participants completed follow-up assessments at 3, 6, 9 and 12 months to ascertain prevalence of violent behavior. Individuals were on average 24.1 years old (SD = 3.3 years) and predominantly male (n = 24, 80%). In this sample , six people (20%) reported engaging in violence during the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Research evidence confirms the highest risk period for violence in individuals with a mental health diagnosis is the 2‐month period following discharge from a mental health facility. Earlier studies of adult populations report that between 1% and 20% of individuals admitted to the hospital for a psychiatric admission are reported to engage in violence once discharged (Rolin et al, 2022). Our data extend this earlier research, with many mothers in our study experiencing violence from their child in the 2 months following their child's initial receipt of a mental health diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Research evidence confirms the highest risk period for violence in individuals with a mental health diagnosis is the 2‐month period following discharge from a mental health facility. Earlier studies of adult populations report that between 1% and 20% of individuals admitted to the hospital for a psychiatric admission are reported to engage in violence once discharged (Rolin et al, 2022). Our data extend this earlier research, with many mothers in our study experiencing violence from their child in the 2 months following their child's initial receipt of a mental health diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…So, early intervention programs in psychosis could implement an identification of patients with early conduct disorders, high impulsivity and CU, as well as trace the onset of CU to identify early and persistent users. The use of tools to assess risk factors for VB [such as the HCR20 ( 146 , 147 )], CU and impulsivity, could be useful. Recent studies have shown the feasibility and value of these tools into mental health services.…”
Section: Discussionmentioning
confidence: 99%